PENGARUH MODIFIKASI PADA ALGORITMA HILL CLIMBING UNTUK PELACAKAN TITIK DAYA MAKSIMUM PHOTOVOLTAIC MENGGUNAKAN SEPIC CONVERTER - Ratih Mar'atus Sholihah; Irwan Mahmudi; Yuli Asmi Rahman; Sundun Sada Maripi (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2023)
Renewable energy is an alternative energy to reduce the use of fossil energy, one of the renewable energy used today is photovoltaic. photovoltaic converts solar energy into electrical energy. The efficiency of photovoltaic is very low, so a method is needed to get the maximum power. The method for getting maximum power from photovoltaic is called Maximum Power Point Tracking (MPPT). MPPT is a method to track the power point of an energy source to produce maximum power. There are various methods and ways to realize MPPT control, one of which is the Modified Hill Climbing Algorithm (MHC) . The algorithm determines the duty cycle setting on the SEPIC Converter. It is intended that the converter work at maximum power. In testing using measurement and calculation data, the average tracking efficiency value = 99.99486%, the average tracking speed value = 0.189978s and the average tracking power value = 50.56408 Watt. Modified Hill Climbing Method provides better tracking power and efficiency when compared to simple Hill Climbing, but makes the Steady state response time 0.1s longer.